Pengaruh Waktu Dan Konsentrasi Polietilen Glikol Dalam Proses Presipitasi Silika Dari Palm Oil Mill Fly Ash (POMFA) - Fitriani Fitriani; Edy Saputra; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Silica precipitation synthesis has been carried out from palm oil mill fly ash waste by using polyethylene glycol as dispersant. This study aims to determine the effect of time and concentration of polyethylene glycol (PEG) on yield and primary particle size of silica. The silica from POMFA was extracted with NaOH. The precipitation process was sodium silicate (Na2SiO3) added with PEG-400 then heated at 70°C, precipitated using CO2 impregnation of 300 ml / minute and mechanical fragmentation of 1000 RPM. The time was variation : 90, 120, 150 and 180 minutes and PEG concentrations was variation : 5%, 10%, 15% and 20%. The silica obtained is separated by filter paper and washed with warm distilled water and dry at 105°C until the weight is constant. The resulting silica was characterization XRD and XRF test to determine the composition and purity of silica. The best time obtained from the precipitation process was at 180 minutes with silica yield of 84.27%, and for the smallest diameter silica primary particle size was obtained with the use of 5% PEG is 19.11 nm.Keywords: Precipitation, Polyethylene Glycol, Silica, yield